Effects of Nutritional Status on the Well-Being and Academic Performance of Grade Five Pupils - Calub, Jennylyn (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effects of nutritional status on the well-being and academic performance of Grade Five pupils in selected public elementary schools in Tanay District during the School Year 2025–2026. It employed a descriptive survey research design complemented by documentary analysis. The respondents consisted of 40 Grade Five teachers and 300 Grade Five pupils selected using Slovin’s formula. Data were gathered through a researcher-made questionnaire assessing the perceived effects of nutritional status on pupils’ physical, emotional, social, and intellectual development, while pupils’ academic performance was determined through documentary analysis of their average grades. Findings revealed that teachers perceived nutritional status to have a very high effect on pupils’ well-being across all developmental domains, whereas pupils rated its effect as high. A significant difference existed between the perceptions of teachers and pupils regarding the effects of nutritional status. Teachers’ perceptions did not significantly differ according to their demographic profile. Among pupils, no significant differences were found based on sex, sibling position, and family size; however, significant differences were observed in terms of monthly family income, parents’ educational attainment, and parents’ occupation. The pupils obtained a Very Satisfactory level of academic performance, and a significant relationship was established between the perceived effects of nutritional status on well-being and academic performance. The study concluded that nutritional status plays a significant role in pupils’ holistic well-being and is positively associated with academic achievement. It further established that socioeconomic factors influence pupils’ perceptions of the effects of nutritional status, while teachers’ demographic characteristics do not. The study recommends the continuous implementation and strengthening of school-based nutrition education programs, the provision of targeted academic intervention activities by teachers, the adoption of the proposed action plan, and the conduct of experimental studies to further examine the causal effects of nutritional status on pupils’ well-being and academic performance..